STRATEGI MEDIATOR DALAM MENCAPAI PERDAMAIAN PADA SENGKETA WARIS (Studi Kasus Putusan Nomor: 1572/Pdt.G/2022/Pa.Ngw) - Bintang Raharja Pangestu; Abdullah Afif (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This research is motivated by the author's curiosity about how the performance of a mediator judge in the Religious Court in handling inheritance dispute cases, where inheritance dispute cases are family problems that are arguably quite complicated, because they involve property in the form of money, land, vehicles and houses. So the inheritance dispute needs to be resolved with the mediator as the mediator of the problem, so that peace can be achieved.The purpose of the research is to analyze how the steps taken by the mediator judge in Case Number 1572/Pdt.G/2022/Pa.Ngw and what are the success factors of the mediator so that peace is achieved in the inheritance dispute case. This research uses qualitative research with a normative approach. The data collection techniques used are documentation and interviews. Then the data that has been collected is analyzed using descriptive analysis method.Based on the results of the analysis that researchers conducted interviews with mediator judges at the Ngawi Religious Court in the case of inheritance dispute Number 1572/Pdt.G/2022/Pa.Ngw. That the steps of the mediator judge in carrying out mediation are still carried out in accordance with the applicable provisions in PERMA No. 1 of 2016. At the beginning of the mediator judge's meeting with the parties, both the plaintiff and the defendant, the mediator must be able to foster a sense of trust in the parties to the dispute, which is the main capital in the mediation step. The division of inheritance is carried out on the basis of mutual agreement of the parties, but before that the mediator conveys in advance the share that will be obtained according to faraidh law. Then there are several factors that become the capital for achieving peace, namely internal and external factors. Internal factors are seen from the parties to the dispute, good faith and wholehearted willingness to be willing to be mediated. External factors are seen from the skills of a mediator who can determine the success of mediation.